2014
DOI: 10.15282/jmes.6.2014.11.0081
|View full text |Cite
|
Sign up to set email alerts
|

Surface Integrity of LM6 Aluminum Metal Matrix Composite when Machined with High Speed Steel and Uncoated Carbide Cutting Tools

Abstract: Metal matrix composite (MMC) is a combination of two or more materials in a metal matrix, and is being widely used nowadays due to its excellent properties. This paper presents the surface integrity of LM6 aluminum MMC when machined with two different cutting tools; high speed steel (HSS) and uncoated carbide. The experiments were carried out with a constant cutting speed, feed rate and axial depth of cut, but differ in the radial depth of cut under dry cutting conditions. Results indicated that machining LM6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…From the image of the AMC IV sample (Figure 3), the worn surface was characterised by the localised shallow grooves and very fine scratches under SEM micrograph. This is due to the load bearing capacity of the particle mixture [7,19]. It is noteworthy that MPS along with Mg element in AMC showed better performance in terms of hardness and wear resistance.…”
Section: Wear Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…From the image of the AMC IV sample (Figure 3), the worn surface was characterised by the localised shallow grooves and very fine scratches under SEM micrograph. This is due to the load bearing capacity of the particle mixture [7,19]. It is noteworthy that MPS along with Mg element in AMC showed better performance in terms of hardness and wear resistance.…”
Section: Wear Analysismentioning
confidence: 93%
“…Aluminium alloys are very soft and have limited properties in terms of hardness and wear resistance, however, these properties can be relatively made highly resistant by introducing predominantly hard but brittle particles such as SiC, Al2O3, and B4C [4]. Recent researches [5][6][7][8][9] have shown that aluminium matrix composite (AMC) possesses desired potential properties such as high specific strength and stiffness, required wear resistance to withstand abrasive properties compared to monolithic materials which are demanded by automotive and aerospace industries for the tribological application. Other researchers [10][11][12][13][14] showed that silicon carbide (SiC) is ideal reinforcement candidate for several matrix materials, including aluminium because of its significant ability to enhance the strength, modulus, thermal stability, and abrasive wear resistance of the matrix materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface roughness is mostly based on the cutting parameters (cutting speed, feed rate, and depth of cut) and sometimes some other parameters [4]. In the literature, various models for the optimum surface roughness have been reported [5][6][7][8][9][10]. The feed rate was found to be the dominant factor among the cutting parameters (cutting speed, feed rate and cutting time) on the surface roughness and flank wear during the turning of AISI H11, using the response surface methodology (RSM) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Metal matrix composites (MMC) have the potential to meet the design requirements of the automobile industry with significant weight saving and a high strength-to-weight ratio [1][2][3]. Recent developments in aluminum-based MMC make it the ideal candidate to replace heavier materials like iron and steel in the car for weight reduction [4].…”
Section: Introductionmentioning
confidence: 99%